High purity sulfonated thiophene monomer

By oxidative polymerization using functionalized thiophene monomers, functionalized π-conjugated polythiophene with high conductivity was prepared, which solved the problems of insufficient conductivity of the conductive layer and poor material performance in the prior art, and achieved more efficient solid electrolyte layer performance.

CN119585339APending Publication Date: 2025-03-07HERAEUS EPURIO GMBH

Patent Information

Application Number
CN202380053784.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-17
Filing Date
2023-08-16
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The conventional π-conjugated polymers have insufficient conductivity when preparing solid electrolyte layers, and the PSS present in the PEDOT/PSS dispersion is a non-conductive inert material, resulting in large particle size, poor penetration, and limited solid content.

Method used

Functionalized π-conjugated polythiophene is prepared by oxidative polymerization using a monomer composition containing functionalized thiophene monomer to form a polymer composition with high conductivity and improve its performance in the conductive layer by specific treatment methods.

Benefits of technology

The conductivity of the conductive layer is significantly improved, the penetration of particles and the solid content of the solids are improved, and the problems of insufficient conductivity and poor material performance in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585339A_ABST
    Figure CN119585339A_ABST
Patent Text Reader

Abstract

The present invention relates to a monomer composition comprising at least one functionalized thiophene monomer having the structure (I) wherein X1 and X2, independently of each other, represent O or S; x3 represents-CH2-O-in which a carbon atom is bonded to R1, or represents-O-; r1 represents a trivalent organic group; r2 represents a divalent organic group; m1 represents a monovalent cation; wherein the monomer composition is substantially free of an unsaturated organic sulfonic acid having the structure (II) wherein R3 represents a divalent organic group; m2 represents a monovalent cation; or wherein the monomer composition comprises an unsaturated organic sulfonic acid having the structure (II) in a maximum amount such that the molar ratio of the total amount of unsaturated organic sulfonic acid having the structure (II) to the total amount of functionalized thiophene monomer having the structure (I) is 1: 32 or less. The invention also relates to a process for the preparation of functionalized pi-conjugated polythiophenes, the functionalized pi-conjugated polythiophenes obtainable by this process, polymer compositions comprising functionalized pi-conjugated polythiophenes, a process for the preparation of lamellar bodies, lamellar bodies obtainable by this process, and methods for the preparation of functionalized pi-conjugated polythiophenes. And the use of the monomer composition or the polymer composition according to the invention for producing an electrically conductive layer in an electronic device. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to monomer compositions comprising functionalized thiophene monomers, methods for preparing functionalized π-conjugated polythiophene, functionalized π-conjugated polythiophene obtained by such methods, polymer compositions comprising functionalized π-conjugated polythiophene, methods for preparing layered bodies, layered bodies obtained by such methods, and the use of monomer compositions or polymer compositions according to the invention for preparing conductive layers in electronic devices.

[0002] Commercially available electrolyte capacitors typically consist of porous metal electrodes, an oxide layer serving as the dielectric on the metal surface, a conductive material (usually solid) introduced into the porous structure, external electrodes (contacts) such as a silver layer, and additional electrical contacts and encapsulation. A commonly used electrolyte capacitor is the tantalum electrolyte capacitor, where the anode electrode is made of valve metal tantalum, on which a uniform tantalum pentoxide dielectric layer has been formed through anodizing (also known as "forming"). A liquid or solid electrolyte forms the cathode of the capacitor. Aluminum capacitors are also frequently used, where the anode electrode is made of valve metal aluminum, on which a uniform electrically insulating aluminum oxide layer has been formed through anodizing as the dielectric. Here, a liquid or solid electrolyte also forms the cathode. Aluminum capacitors are typically constructed as wound capacitors or stacked capacitors.

[0003] π-conjugated polymers are particularly suitable as solid electrolytes in the aforementioned capacitors due to their high electrical conductivity. π-conjugated polymers are also known as conductive polymers or synthetic metals. Their economic importance is increasing because polymers are superior to metals in terms of processability, weight, and the ability to selectively tune their properties through chemical modification. Known examples of π-conjugated polymers are polypyrrole, polythiophene, polyaniline, polyacetylene, polyphenylene, and poly(p-phenylenevinylene). A particularly important polythiophene used industrially is poly(3,4-ethylenedioxythiophene) (PEDOT) because of its very high electrical conductivity in its oxidized form.

[0004] Solid electrolytes based on conductive polymers can be applied to oxide layers by various methods. For example, EP-A-0 340512 describes the production of a solid electrolyte from 3,4-ethylenedioxythiophene and its use in electrolyte capacitors. According to the teachings of this disclosure, 3,4-ethylenedioxythiophene is polymerized in situ onto an oxide layer. In addition to in-situ polymerization, there are methods for producing solid electrolytes in capacitors, wherein a dispersion comprising polymerized thiophene and a polyanion (e.g., from a PEDOT / PSS dispersion (PEDOT = poly(3,4-ethylenedioxythiophene); PSS = polystyrene sulfonic acid)) as a counterion is applied to an oxide layer, and the dispersant is then removed by evaporation, which is also known from the prior art. Such methods for producing solid electrolyte capacitors are disclosed, for example, in DE-A-10 2005 043 828.

[0005] However, PEDOT / PSS dispersions are characterized by the drawback of containing a large amount of PSS as a non-conductive inert material. Furthermore, due to the presence of PSS, the size of the PEDOT / PSS particles in the dispersion is sometimes too large to ensure that the particles also penetrate the smaller pores of the porous metal electrode. Finally, the maximum solids content of PEDOT / PSS dispersions is typically limited to about 3% by weight. To overcome these drawbacks, liquid compositions containing PEDOT derivatives have been prepared, characterized by not having the known disadvantages of PEDOT / PSS dispersions. Polythiophenes functionalized with sulfonic acid groups were initially developed. Due to the sulfonic acid groups, these polythiophenes are self-doped and do not require counterions such as PSS.

[0006] For example, EP 1 122 274 A1 and US 9,781,905 B2 disclose the preparation of functionalized π-conjugated polymers such as poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-ylmethoxy)-1-butanesulfonic acid) or poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-ylmethoxy)-2-butanesulfonic acid) (in the scientific literature, both polymers are referred to as "PEDOT-S" or "S-PEDOT"). These monomers are prepared by oxidative polymerization of the corresponding monomers 4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-ylmethoxy)-1-butanesulfonic acid and 4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-ylmethoxy)-2-butanesulfonic acid (EDOT-S) (in the scientific literature, the two monomers are referred to as "EDOT-S" or "S-EDOT"). These monomers are typically prepared by sulfonating thieno[3,4-b]-1,4-dioxin-2-methanol ("EDOT-MeOH") with 1,4-butanesulfonate lactone (for 1-butanesulfonic acid derivatives) or 2,4-butanesulfonate lactone (for 2-butanesulfonic acid derivatives), respectively, with a mixture of EDOT-MeOH and 3,4-(2-hydroxypropyldioxy)-thiophene ("ProDOT-MeOH").

[0007] However, the conductivity of conductive layers prepared from polymer solutions obtained by these methods still needs improvement, especially if these polymer solutions are used to prepare solid electrolyte layers, for example, in solid electrolyte capacitors.

[0008] Therefore, one object of the present invention is to overcome the shortcomings of the prior art in the field of π-combined polymers.

[0009] In particular, an object of the present invention is to provide polymer compositions comprising π-conjugated conductive polymers, preferably compositions comprising water-soluble or water-dispersible π-conjugated conductive polymers, and even more preferably PEDOT-S-compositions, characterized in that the conductive layers prepared by means of these polymer compositions exhibit increased conductivity compared to corresponding compositions known in the art.

[0010] The contribution to the solution to at least one of the above objectives is provided by the subject matter of the independent claims forming the class, wherein the dependent claims that depend thereon represent preferred embodiments of the invention, the subject matter of which also contributes to solving at least one objective.

[0011] |1a| The first embodiment, which includes at least one functionalized thiophene monomer having structure I, also contributes to solving at least one of the objectives according to the invention:

[0012]

[0013] in

[0014] X 1 and X 2 Each can be represented independently as O or S, preferably O;

[0015] X 3 It represents CH2-O, in which carbon atoms are bonded to R. 1 , or O;

[0016] R 1 It represents a trivalent organic group, preferably a saturated, straight-chain or branched trivalent hydrocarbon group;

[0017] R 2 This indicates a divalent organic group, preferably a saturated, straight-chain, or branched alkylene group;

[0018] M 1 This refers to a monovalent cation, preferably a monovalent cation selected from the group consisting of: H + NH4 + Tetraalkylamine or alkali metal cations, more preferably monovalent cations selected from the group consisting of: H + and Na + The most preferred option is Na. + ;

[0019] The monomer composition is substantially free of unsaturated organic sulfonic acids having structure II.

[0020]

[0021] in

[0022] R 3 This indicates a divalent organic group, preferably a saturated, straight-chain, or branched alkylene group;

[0023] M 2 This refers to a monovalent cation, preferably a monovalent cation selected from the group consisting of: H + NH4 + Tetraalkylamine or alkali metal cations, more preferably monovalent cations selected from the group consisting of: H + and Na + The most preferred option is Na. + Further preferably, M is present in the given composition. 1 and M 2 They are at least to some extent the same;

[0024] Alternatively, the monomer composition may contain an unsaturated organic sulfonic acid having structure II, the maximum amount of which is such that the molar ratio of the total amount of the unsaturated organic sulfonic acid having structure II to the total amount of the functionalized thiophene monomer having structure I is 1:32 or less, preferably 1:52 or less, more preferably 1:82 or less, even more preferably 1:112 or less, even more preferably 1:132 or less, and most preferably 1:152 or less.

[0025] As used herein, the term "substantially free of" in relation to the amount of unsaturated organic sulfonic acid having structure II preferably means when, according to the methods disclosed herein, 1 When analyzing the composition by ¹H NMR, such unsaturated organic sulfonic acids are included in the monomer composition according to the invention in amounts below the detection limit. In a particularly preferred embodiment of the composition according to the invention, the monomer composition does not contain unsaturated organic sulfonic acids having structure II.

[0026] It has been observed that EDOT-S monomers, known in the art as prepared by reacting EDOT-MeOH or a mixture of EDOT-MeOH and ProDOT-MeOH with sulfonyl lactones such as 1,4-butanesulfonyl lactone, contain a certain amount of unsaturated organic sulfonic acid with structure II. Surprisingly, it has also been observed that conductive layers prepared by polymerizing thiophene monomers containing a certain amount of such unsaturated organic sulfonic acid exhibit significantly lower conductivity compared to conductive layers prepared by polymerizing functionalized π-conjugated polythiophene, in which the content of such unsaturated organic sulfonic acid is below a certain maximum amount. Therefore, unsaturated organic sulfonic acids appear to interfere with the polymerization process.

[0027] |2a| In a preferred embodiment of the monomer composition according to the invention, the monomer composition comprises a functionalized thiophene monomer having structure Ia or structure Ib, or a mixture comprising functionalized thiophene monomers having structure Ia or Ib.

[0028]

[0029] In equations Ia and Ib

[0030] -m is 2, R 3 For -CH3 and M 1 Preferably Na + ;

[0031] or

[0032] -m is 3, R 3 For H and M 1 Preferably Na + .

[0033] Therefore, the functionalized thiophene monomer is preferably sodium 4-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]butane-1-sulfonate or sodium 4-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]butane-2-sulfonate. In this context, it is also preferred that the unsaturated organic sulfonic acid having structure II is sodium 3-butene-1-sulfonate (in the case of sodium 4-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]butane-1-sulfonate) or sodium 3-butene-2-sulfonate (in the case of sodium 4-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]butane-2-sulfonate). This preferred embodiment is a second embodiment of the monomer composition according to the invention, which preferably depends on the first embodiment.

[0034] |3a| In another preferred embodiment of the monomer composition according to the invention, m is 3 in formulas Ia and Ib, and R 3 For H and M 1 Preferably Na + Therefore, according to this preferred embodiment, at least one functionalized thiophene monomer is 4-(2,3-dihydrothiophene[3,4-)

[0035] [b][1,4]dioxin-2-ylmethoxy)-1-butanesulfonate sodium, wherein the monomer composition may further comprise a mixture of EDOT-S and ProDOT-S as a functionalized thiophene monomer. In this context, an unsaturated organic sulfonic acid having structure II, namely 3-butene-1-sulfonate sodium (i.e., R...), is also preferred. 3 (for -CH2-CH2-). This preferred embodiment is a third embodiment of the monomer composition according to the invention, which preferably depends on the first or second embodiment.

[0036] |4a| In another preferred embodiment of the monomer composition according to the invention, at least one functionalized thiophene monomer is a mixture of functionalized thiophene monomers having structure Ia or Ib, wherein the weight ratio of the monomer having structure Ia to the monomer having structure Ib in the monomer composition (i.e., the weight ratio of EDOT-S to ProDOT-S) is at least 4:1, preferably at least 6:1, more preferably at least 8:1, even more preferably at least 10:1, even more preferably at least 25:1, even more preferably at least 50:1, and most preferably at least 100:1. This preferred embodiment is a fourth embodiment of the monomer composition according to the invention, which preferably depends on the second or third embodiment.

[0037] |5a| In another preferred embodiment of the monomer composition according to the invention, the monomer composition comprises a functionalized thiophene monomer having structure I, the total amount of which, in each case, is at least 90 wt%, preferably at least 92.5 wt%, even more preferably at least 95 wt%, even more preferably at least 96 wt%, even more preferably at least 97 wt%, even more preferably at least 98 wt%, even more preferably at least 99 wt%, even more preferably at least 99.5 wt%, and most preferably at least 99.9 wt%. This preferred embodiment is a fifth embodiment of the monomer composition according to the invention, which preferably depends on any one of the first to fourth embodiments.

[0038] |6a| In another preferred embodiment of the monomer composition according to the invention, the monomer composition satisfies at least one of the following properties i) and ii), preferably both of them:

[0039] i) The monomer composition has a color value b* of less than 0.75, preferably less than 0.70, more preferably less than 0.65 as determined according to ASTM E 308-13, the color value being determined in a 0.5 mm transmission quartz glass cuvette using an aqueous solution containing at least one functionalized thiophene monomer having structure I in a total amount of 1 wt%.

[0040] ii) The transmittance of the monomer composition to light with a wavelength of 350 nm is at least 90%, preferably at least 91%, more preferably at least 93%, even more preferably at least 94%, even more preferably at least 95%, and even more preferably at least 96%.

[0041] This preferred embodiment is a sixth embodiment of the monomeric composition according to the invention, which preferably depends on the fifth embodiment.

[0042] The monomer composition according to the present invention, preferably the monomer composition according to the fifth or sixth embodiment thereof, can be prepared by means of a method comprising the following steps:

[0043] A) Provides a liquid composition comprising a thiophene alkoxy precursor monomer having structure III.

[0044]

[0045] in

[0046] X 1 and X 2 Each can be represented independently as O or S, preferably O;

[0047] X 4 Indicates CH2-O- In which carbon atoms are bonded to R 1 , or to represent O - ;

[0048] R 1 It represents a trivalent organic group, preferably a saturated, straight-chain or branched trivalent hydrocarbon group;

[0049] B) Reacting a thiophene alkoxy precursor monomer having structure III with a sulfonyl lactone having structure IV.

[0050]

[0051] To obtain a reaction mixture comprising at least one functionalized thiophene monomer having structure I, wherein R 2 This indicates a divalent organic group, preferably a saturated, straight-chain, or branched alkylene group;

[0052] C) Separate the functionalized thiophene monomer with structure I in solid form from the reaction mixture;

[0053] D) Dissolve or disperse the purified thiophene monomer obtained in step C) in water to obtain an aqueous solution or dispersion, preferably an aqueous solution, wherein the aqueous solution or dispersion preferably contains at least 20% by weight, more preferably at least 30% by weight, even more preferably at least 40% by weight, and most preferably at least 50% by weight of a functionalized thiophene monomer having structure I based on the total weight of the aqueous solution or dispersion in each case.

[0054] E) Provide C1-C5 alcohols, preferably alcohols selected from the group consisting of: methanol, ethanol,

[0055] 1-Propanol, 2-Propanol, 1-Butanol, 2-Butanol, Isobutanol, tert-Butanol, 1-Pentanol, 2-Pentanol, 3-Pentanol, 2-Methyl-1-Butanol, 2-Methyl-2-Butanol, 3-Methyl-1-Butanol, 3-Methyl-2-Butanol, 2,2-Dimethyl-1-Propanol, or a mixture of at least two of these alcohols, more preferably alcohols selected from the group consisting of ethanol and 1-butanol, optionally cooling the alcohol to a temperature below -10°C, preferably below -15°C, and even more preferably below -20°C, and adding an aqueous solution or dispersion containing a functionalized thiophene monomer having structure I obtained in step D) to the alcohol to obtain an alcohol solution or dispersion, which (particularly if the alcohol is not pre-cooled) can be cooled to a temperature below -10°C, preferably below -15°C, and even more preferably below -20°C, thereby obtaining a precipitate containing a purified thiophene monomer having structure I;

[0056] F) Separate the precipitate from the alcohol solution or dispersion obtained in step G) to obtain the monomer composition according to the invention.

[0057] In the methods disclosed above, the monomer composition obtained in step F) can be further purified by a method including the following steps:

[0058] G) Dissolve or disperse the purified thiophene monomer obtained in step F) in water to obtain an aqueous solution or dispersion (containing a functionalized thiophene monomer having structure I), preferably an aqueous solution, wherein the aqueous solution or dispersion preferably contains at least 20% by weight, more preferably at least 30% by weight, even more preferably at least 40% by weight, and most preferably at least 50% by weight of the functionalized thiophene monomer having structure I based on the total weight of the aqueous solution or dispersion in each case.

[0059] H) Cool the aqueous solution or dispersion obtained in step G) to a temperature not exceeding 15°C, preferably not exceeding 13°C, and most preferably not exceeding 10°C, thereby reprecipitating the functionalized thiophene monomer having structure I.

[0060] I) Separate the precipitate from the aqueous solution or dispersion to obtain the monomer composition according to the invention.

[0061] |1b| First method of preparing a polymer composition comprising functionalized π-conjugated polythiophene

[0062] The implementation scheme also contributes to solving at least one of the objectives according to the present invention, the method comprising the following method steps:

[0063] I) Dissolve or disperse the monomer composition according to the invention, preferably the monomer composition according to any one of the first to sixth embodiments, in a solvent or dispersant, preferably in water, to obtain a solution or dispersion of the functionalized thiophene monomer.

[0064] II) Oxidatively polymerizing a functionalized thiophene monomer having structure I in the solution or dispersion provided in step I) to obtain a polymer composition in solution or dispersion form, the polymer composition comprising a functionalized π-conjugated polythiophene containing repeating units having structure I'.

[0065]

[0066] The asterisk (*) indicates a bond with an adjacent repeating unit, and X... 1 X 2 X 3 R 1 R 2and M 1 As defined for the functionalized thiophene monomer in the monomer composition according to the present invention;

[0067] III) Optionally purify the solution or dispersion of the functionalized π-conjugated polythiophene obtained in step II), preferably by means of ion filtration.

[0068] IV) Optionally dilute the solution or dispersion of the functionalized π-conjugated polythiophene contained in step II) or obtained in step III), preferably with water.

[0069] |2b| In a preferred embodiment of method 1 according to the invention, the solution or dispersion provided in step I) comprises a functionalized thiophene monomer having structure I, the amount of which in each case ranges from 1 wt% to 50 wt%, preferably from 5 wt% to 40 wt%, and more preferably from 10 wt% to 30 wt%, based on the total weight of the solution or dispersion provided in step I). This preferred embodiment is a second embodiment of method 1 according to the invention, which preferably depends on the first embodiment.

[0070] |3b| In another preferred embodiment of method 1 according to the invention, the solution or dispersion provided in step I) further comprises at least one oxidizing agent. This preferred embodiment is a third embodiment of method 1 according to the invention, which preferably depends on the first or second embodiment.

[0071] |4b| In another preferred embodiment of method 1 according to the invention, the solution or dispersion provided in step I) is an aqueous solution or dispersion, and the pH of the aqueous solution or dispersion provided in step I) is adjusted to a value less than 2.5, preferably less than 2.0, and more preferably less than 1.5 using an organic or inorganic acid. The organic or inorganic acid is preferably an acid selected from the group consisting of formic acid, acetic acid, lactic acid, propionic acid, citric acid, malic acid, fumaric acid, sulfuric acid, sulfonic acid, nitric acid, phosphonic acid, phosphoric acid, or a mixture of at least two of these acids, with sulfuric acid being particularly preferred. This preferred embodiment is a fourth embodiment of method 1 according to the invention, which preferably depends on any one of the first to third embodiments.

[0072] |5b| In another preferred embodiment of method 1 according to the invention, the oxidative polymerization in step II) is carried out under an inert gas atmosphere of nitrogen, argon, carbon dioxide, or a mixture thereof. This preferred embodiment is a fifth embodiment of method 1 according to the invention, which preferably depends on the first to fourth embodiments.

[0073] |6b| In another preferred embodiment of method 1 according to the invention, the oxidative polymerization in step II) is carried out at a pressure equal to or higher than the vapor pressure of the aqueous solution or dispersion during the polymerization reaction in step II). This preferred embodiment is a sixth embodiment of method 1 according to the invention, which preferably depends on any one of the first to fifth embodiments.

[0074] |7b| In another preferred embodiment of method 1 according to the invention, the oxidative polymerization in step II) is carried out at a reduced pressure not exceeding 0.8 bar. This preferred embodiment is a seventh embodiment of method 1 according to the invention, which preferably depends on any one of the first to sixth embodiments.

[0075] |8b| In another preferred embodiment of method 1 according to the invention, purification in step III) is accomplished by means of filtration and / or by means of treatment with an ion exchanger. This preferred embodiment is an eighth embodiment of method 1 according to the invention, which preferably depends on any one of the first to seventh embodiments.

[0076] |9b| In another preferred embodiment of method 1 according to the invention, the dilution in step IV) is performed to such an extent that the solids content of the polymer composition, in each case, is in the range of 0.1% to 25% by weight, preferably in the range of 0.25% to 10% by weight, and more preferably in the range of 0.5% to 5% by weight, based on the total weight of the polymer composition. This preferred embodiment is a ninth embodiment of method 1 according to the invention, which preferably depends on any one of the first to eighth embodiments.

[0077] The first embodiment of polymer composition 1 also addresses the issue of [the objective of the invention]...

[0078] One less objective has been achieved: the polymer composition comprises a functionalized π-conjugated polythiophene that can be obtained by method 1 according to the invention, preferably by method 1 according to any one of the first to ninth embodiments. Preferably, the functionalized π-conjugated polythiophene obtained by method 1...

[0079] The obtained functionalized π-conjugated polythiophene is dissolved or dispersed in water as a solvent or dispersant. |1d| The first embodiment of the polymer composition 2 containing functionalized π-conjugated polythiophene also has the effect of dissolving...

[0080] The invention contributes to at least one of the objectives of the present invention, wherein the functionalized π-conjugated polythiophene comprises repeating units having structure I'.

[0081]

[0082]

[0083] in

[0084] X 1 and X 2 Each can be represented independently as O or S, preferably O;

[0085] X 3 It represents CH2-O, in which carbon atoms are bonded to R. 1 , or O;

[0086] R 1 It represents a trivalent organic group, preferably a saturated, straight-chain or branched trivalent hydrocarbon group;

[0087] R 2 This indicates a divalent organic group, preferably a saturated, straight-chain, or branched alkylene group;

[0088] M 1 This refers to a monovalent cation, preferably a monovalent cation selected from the group consisting of: H + NH4 + Tetraalkylamine or alkali metal cations, more preferably monovalent cations selected from the group consisting of: H + and Na + The most preferred option is Na. + ;

[0089] The asterisk (*) indicates a bond with an adjacent repeating unit;

[0090] Functionalized π-conjugated polythiophene essentially contains no repeating units with structure II'.

[0091]

[0092] in

[0093] R 3 This indicates a divalent organic group, preferably a saturated, straight-chain, or branched alkylene group;

[0094] M 2This refers to a monovalent cation, preferably a monovalent cation selected from the group consisting of: H + NH4 + Tetraalkylamine or alkali metal cations, more preferably monovalent cations selected from the group consisting of: H + and Na + The most preferred option is Na. + Further preferred is M in a given functionalized π-conjugated polythiophene. 1 and M 2 They are at least to some extent the same;

[0095] The asterisk (*) indicates a bond with an adjacent repeating unit;

[0096] Alternatively, the functionalized π-conjugated polythiophene may contain repeating units having structure II' in such a large quantity that the molar ratio of the total amount of repeating units having structure II' to the total amount of repeating units having structure I' is 1:32 or less, preferably 1:52 or less, more preferably 1:82 or less, even more preferably 1:112 or less, even more preferably 1:132 or less, and most preferably 1:152 or less.

[0097] As used herein, the term "substantially free of" relating to the amount of repeating units having structure II' preferably means when, according to the method disclosed herein, by 1 When analyzing the composition by ¹H NMR, such repeating units are included in the functionalized π-conjugated polythiophene contained in the polymer composition 2 according to the invention in amounts below the detection limit. In a particularly preferred embodiment of the composition according to the invention, the functionalized π-conjugated polythiophene does not contain repeating units having structure II'.

[0098] Furthermore, as used herein, the term "polymer composition 2" preferably refers to any composition comprising functionalized π-conjugated polythiophene containing repeating units having structure I', regardless of its polymerization state. Thus, polymer composition 2 can be, for example, a dispersion or solution in which the functionalized π-conjugated polythiophene is dissolved or dispersed in a solvent or dispersant, or it can be a conductive layer formed by applying such a solution or dispersion to a substrate and subsequently removing the solvent or dispersant.

[0099] |2d| In a preferred embodiment of the polymer composition 2 according to the invention, the functionalized π-conjugated polythiophene comprises repeating units having structure Ia' or structure Ib' or a mixture comprising repeating units having structure Ia' or Ib'.

[0100]

[0101] In equations Ia' and Ib'

[0102] -m is 2, R 3 For -CH3 and M 1 Preferably Na + ;

[0103] or

[0104] -m is 3, R 3 For H and M 1 Preferably Na + .

[0105] Therefore, the functionalized π-conjugated polythiophene is preferably poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]butane-1-sulfonate) or poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]butane-2-sulfonate). In this context, residue R in the repeating unit having structure II' is also preferred. 3 The -CH2-CH2- group (in the case of poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]butane-1-sulfonate) or the -CHCH3- group (in the case of poly(4-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]butane-2-sulfonate) is a second embodiment of the polymer composition 2 according to the invention, which preferably depends on the first embodiment.

[0106] In another preferred embodiment of the polymer composition 2 according to the invention, m is 3 in formulas Ia' and Ib', and R... 3 For H and M 1 Preferably Na + Therefore, according to this preferred embodiment, the functionalized π-conjugated polythiophene is poly(4-(2,3-dihydrothiophene)).

[0107] [3,4-b][1,4]dioxin-2-ylmethoxy)-1-butanesulfonate sodium salt), wherein the functionalized π-conjugated polythiophene may further comprise a mixture of EDOT-S and ProDOT-S as repeating units. In this context, residue R in the repeating unit having structure II' is also preferred. 3 for-

[0108] CH2-CH2- group. This preferred embodiment is a third embodiment of the polymer composition 2 according to the invention, which preferably depends on the first or second embodiment.

[0109] In another preferred embodiment of the polymer composition 2 according to the invention, the functionalized π-conjugated polythiophene comprises a mixture of repeating units having structures Ia' or Ib', wherein the weight ratio of repeating units having structure Ia' to repeating units having structure Ib' in the functionalized π-conjugated polythiophene is at least 4:1, preferably at least 6:1, more preferably at least 8:1, even more preferably at least 10:1, even more preferably at least 25:1, even more preferably at least 50:1, and most preferably at least 100:1. This preferred embodiment is a fourth embodiment of the polymer composition 2 according to the invention, which preferably depends on the second or third embodiment.

[0110] In another preferred embodiment of the polymer composition 2 according to the invention, the polymer composition is a liquid polymer composition further comprising at least one solvent or dispersant, wherein the liquid polymer composition preferably comprises functionalized π-conjugated polythiophene in an amount ranging from 0.1 wt% to 25 wt% based on the total weight of the liquid polymer composition in each case, more preferably from 0.25 wt% to 10 wt%, and most preferably from 0.5 wt% to 5 wt%. The solvent or dispersant is preferably selected from the group consisting of: water; aliphatic alcohols such as methanol, ethanol, isopropanol and butanol, diacetone alcohol, ethylene glycol and glycerol; aliphatic ketones such as acetone and methyl ethyl ketone; aliphatic nitriles such as acetonitrile; ethylene glycol ethers such as polyethylene glycol methyl ether; and mixtures of at least two of these solvents, particularly mixtures of water and water-miscible solvents, wherein water is most preferably used as the solvent. Such liquid polymer compositions can be obtained, for example, by method 1 according to the invention and are preferably aqueous solutions or dispersions. This preferred embodiment is a fifth embodiment of the polymer composition 2 according to the present invention, which preferably depends on any one of the first to fourth embodiments.

[0111] |6d| In another preferred embodiment of the polymer composition 2 according to the invention, the polymer composition comprises additional additives, preferably selected from the group consisting of: surfactants, adhesion promoters, conductivity-increasing additives, organic binders, or mixtures of at least two of these additional additives. This preferred embodiment is a sixth embodiment of the polymer composition 2 according to the invention, which preferably depends on any one of the first to fifth embodiments, more preferably depending on the fifth embodiment.

[0112] |7d| In another preferred embodiment of the polymer composition 2 according to the invention, the functionalized π-conjugated polythiophene is present in particulate form, wherein the particle size distribution of these particles is characterized by,

[0113] i)d 50 The weight-average particle size (WMP) is in the range of 1 nm to 100 nm, preferably in the range of 1 nm to 80 nm, more preferably in the range of 1 nm to 60 nm, and most preferably in the range of 5 nm to 40 nm.

[0114] as well as

[0115] ii)d 90 The value is less than 3.5 × d 50 Preferably less than 3×d 50 And more preferably less than 2×d 50 of.

[0116] This preferred embodiment is a seventh embodiment of the polymer composition 2 according to the present invention, which preferably depends on the fifth or sixth embodiment.

[0117] |8d| In another preferred embodiment of the polymer composition 2 according to the invention, the functionalized π-conjugated polythiophene is characterized by a mass-average molecular weight M w With molar average molecular weight M n The ratio (M) w / M n The number of components is at least 6, preferably at least 8, more preferably at least 10, more preferably at least 12, more preferably at least 14, more preferably at least 16, more preferably at least 18, and more preferably at least 20. This preferred embodiment is an eighth embodiment of the polymer composition 2 according to the invention, which preferably depends on any one of the fifth to seventh embodiments.

[0118] |9d| In another preferred embodiment of the polymer composition 2 according to the invention, the polymer

[0119] The polymer composition is a conductive layer comprising a functionalized π-conjugated polythiophene, the amount of which, in each case, is in the range of 50% to 99.9% by weight, preferably in the range of 60% to 99.5% by weight, and more preferably in the range of 70% to 99% by weight, based on the total weight of the conductive layer. Such polymer compositions can be obtained, for example, by method 2 according to the invention as described below. This preferred embodiment is a ninth embodiment of polymer composition 2 according to the invention, which preferably depends on any one of the first to fourth embodiments.

[0120] |10d| In another preferred embodiment of the polymer composition 2 according to the invention, by

[0121] The conductive layer made from the polymer composition has a conductivity of at least 250 S / cm, preferably at least...

[0122] The conductivity is 350 S / cm, and more preferably at least 450 S / cm. This preferred embodiment is a tenth embodiment of the polymer composition 2 according to the invention, which preferably depends on the ninth embodiment.

[0123] |1e| A first embodiment of method 2 for preparing a lamellar body also contributes to solving at least one of the objectives according to the invention, the method comprising the following steps:

[0124] A) Provide the substrate;

[0125] B) Apply the polymer composition 1 or polymer composition 2 according to the invention, preferably the polymer composition 2 according to any one of the fifth to eighth embodiments, to at least a portion of at least one surface of the substrate;

[0126] C) Optionally, at least partially remove the solvent or dispersant used to form a conductive layer that covers at least a portion of at least one surface of the substrate.

[0127] |2e| In a preferred embodiment of method 2 according to the invention, the substrate is an electrode body of an electrode material, wherein a dielectric at least partially covers one surface of the electrode material when forming an anode body. This preferred embodiment is a second embodiment of method 2 according to the invention, which preferably depends on the first embodiment.

[0128] The |1f| layer also contributes to solving at least one of the objectives according to the invention, which can be obtained by method 2 according to the invention, preferably by method 2 according to the first embodiment or the second embodiment.

[0129] |1g| Using the monomeric composition according to the invention or the polymeric composition 1 or polymeric composition 2 according to the invention, preferably the polymeric composition 2 according to any one of the fifth to eighth embodiments thereof, to prepare a conductive layer in an electronic device also contributes to solving at least one of the objectives according to the invention.

[0130] |2g| In a preferred embodiment of the use according to the invention, the electronic device is selected from the group consisting of: OLED, coated fabric, photoconductive cell, photoresistor, photoelectric switch, phototransistor, phototube, IR detector, optoelectronic device, solar cell, coating material for memory storage device, field-effect resistor device, antistatic film, biosensor, electrochromic device, solid electrolyte capacitor, energy storage device, touch panel, and electromagnetic shielding. This preferred embodiment is a second embodiment of the use according to the invention, which preferably depends on the first embodiment.

[0131] |3g| In another preferred embodiment of the use according to the invention, the conductive layer is a solid electrolyte layer in a polymer electrolyte capacitor or a hybrid electrolyte capacitor. This preferred embodiment is a third embodiment of the use according to the invention, which preferably depends on the first or second embodiment.

[0132] According to method 1 of the present invention

[0133] Method 1 for preparing a polymer composition comprising functionalized π-conjugated polythiophene also contributes to achieving at least one of the objectives according to the invention, the method comprising the following steps:

[0134] I) The monomer composition according to the invention, preferably the monomer composition according to any one of the first to sixth embodiments, is dissolved or dispersed in a solvent or dispersant.

[0135] Preferably in water, to obtain a solution or dispersion of the functionalized thiophene monomer;

[0136] II) Oxidatively polymerizing a functionalized thiophene monomer having structure I in the solution or dispersion provided in step I) to obtain a polymer composition in solution or dispersion form, the polymer composition comprising a functionalized π-conjugated polythiophene containing repeating units having structure I'.

[0137]

[0138] The asterisk (*) indicates a bond with an adjacent repeating unit, and X... 1 X 2 ,

[0139] X 3 R 1 R 2 and M 1 As defined for the functionalized thiophene monomer in the monomer composition according to the present invention;

[0140] III) Optionally purify the solution or dispersion of the functionalized π-conjugated polythiophene obtained in step II), preferably by means of ion filtration.

[0141] IV) Optionally dilute the solution or dispersion of the functionalized π-conjugated polythiophene contained in step II) or obtained in step III), preferably with water.

[0142] The oxidation reaction carried out in step II of the method can be catalyzed by a chemical oxidant, by electrochemical oxidation, or by a combination of both. In the case of electrochemical oxidation, the electrode acts as the oxidant.

[0143] Suitable oxidants for use as chemical oxidants are salts of heavy metals, preferably iron salts, more preferably FeCl3, and iron(III) salts of aromatic and aliphatic sulfonic acids, H2O2, K2Cr2O7, salts of peroxydisulfate such as K2S2O8, Na2S2O8, KMnO4, alkali metal perborates, and alkali metal or ammonium persulfates, or mixtures of these oxidants. Salts of heavy metals, salts of peroxydisulfate, or mixtures thereof are particularly preferred. Other suitable oxidants are described, for example, in Handbook of Conducting Polymers (Ed. Skotheim, TA), Marcel Dekker: New York, 1986, Vol. 1, pp. 46-57. Particularly preferred oxidant b) is a salt of peroxydisulfate, particularly K₂S₂O₈ or Na₂S₂O₈; an iron salt, particularly ferric chloride (III); or a mixture of a salt of peroxydisulfate and at least one other compound that catalyzes the cracking of peroxydisulfate, such as a mixture of peroxydisulfate and iron salts. According to a particularly preferred embodiment of the method according to the invention, the oxidant is a mixture of Fe₂(SO₄)₃ and Na₂S₂O₈.

[0144] Suitable solvents or dispersants that can be used in Method 1 according to the invention are water, water-miscible solvents, and especially those selected from the group consisting of: aliphatic alcohols such as methanol, ethanol, isopropanol and butanol, diacetone alcohol, ethylene glycol and glycerol; aliphatic ketones such as acetone and methyl ethyl ketone; aliphatic nitriles such as acetonitrile; ethylene glycol ethers such as polyethylene glycol methyl ether, or mixtures of at least two of these solvents, especially mixtures of water and water-miscible solvents. However, the most preferred solvent or dispersant is water. When 4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-ylmethoxy)-1-butanesulfonic acid or 4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-ylmethoxy)-2-butanesulfonic acid is used as the thiophene monomer, Method 1 according to the invention can therefore produce aqueous solutions or dispersions containing functionalized π-conjugated polythiophenes.

[0145] The concentration of the functionalized thiophene monomer in the solution or dispersion provided in step I) is preferably in the range of 1% to 50% by weight, more preferably in the range of 5% to 40% by weight, and more preferably in the range of 10% to 30% by weight, based on the total weight of the solution or dispersion in each case.

[0146] Different methods exist for preparing the solution or dispersion provided in step I). The functionalized thiophene monomer may be dissolved or dispersed in a solvent or dispersant, followed by the addition of an oxidant (which may also be dissolved or dispersed alone in the solvent or dispersant), or the oxidant may be dissolved or dispersed first in the solvent or dispersant, followed by the addition of the functionalized thiophene monomer (which may also be dissolved or dispersed alone in the solvent or dispersant). If more than one oxidant is used, such as a mixture of Fe2(SO4)3 and Na2S2O8, it may also be possible to first mix one of these components with the functionalized thiophene monomer and the solvent or dispersant, and finally add a second oxidant.

[0147] The polymerization reaction in step II of the method is preferably carried out at a temperature in the range of -20°C to 200°C, preferably 0°C to 100°C, and lasts preferably from 1 hour to 48 hours, more preferably from 5 hours to 20 hours.

[0148] After the polymerization reaction is complete, for further purification purposes, the solution or dispersion containing the functionalized π-conjugated polymer, preferably an aqueous solution containing the functionalized π-conjugated polymer, may be further purified, for example by filtration, particularly by ultrafiltration, and / or by treatment with an ion exchanger in another method step III), particularly by treatment with an anion exchanger and a cation exchanger. Additional additives as described below with respect to Method 1 according to the invention may also be added.

[0149] Furthermore, the solution or dispersion containing the functionalized π-conjugated polymer obtained in step II) and / or after purification in step III), preferably an aqueous solution containing the functionalized π-conjugated polymer, may be further diluted in another step IV), preferably using any of the solvents or dispersants mentioned above with respect to step II), more preferably water. With the aid of such dilution steps, the solids content of the solution or dispersion is preferably adjusted to be in the range of 0.1% to 25% by weight, preferably in the range of 0.25% to 10% by weight, and more preferably in the range of 0.5% to 5% by weight, based on the total weight of the solution or dispersion in each case.

[0150] Furthermore, since the functionalized π-conjugated polythiophene obtained after polymerization in step II) is typically in particulate form, the particle size distribution of the functionalized π-conjugated polythiophene in the solution or dispersion obtained in step II) or after further purification and or after dilution in step III) or step IV) can be adjusted by: ultrasonically treating the solution or dispersion, wherein the energy input is preferably between 10 W / L and 1000 W / L, more preferably between 20 W / L and 500 W / L, and the ultrasonic frequency is preferably... The kHz range is selected to be between 20 kHz and 200 kHz; the oscillation is achieved by homogenizing the solution or dispersion with high pressure, wherein preferably, pressures above 100 bar are applied multiple times, preferably above 500 bar, and most preferably above 1500 bar; or by heat treatment of the solution or dispersion, wherein the heat treatment preferably includes treating the solution or dispersion at a temperature in the range of 40°C to 100°C, preferably at a temperature in the range of 50°C to 95°C for 5 minutes to 100 hours, preferably 1 hour to 10 hours, and more preferably for a duration of 2 hours to 8 hours.

[0151] According to a particularly preferred embodiment of method 1 according to the invention, it is also advantageous that the oxygen content of the solution or dispersion provided in step I) is, in each case, less than 1,000 ppm based on the total weight of the solution or dispersion, preferably less than 500 ppm, more preferably less than 100 ppm, more preferably less than 10 ppm, more preferably less than 1 ppm, more preferably less than 0.5 ppm, and most preferably less than 0.25 ppm. According to a particularly preferred embodiment of method 1 according to the invention, the solution or dispersion provided in step I) is completely free of any oxygen (i.e., the oxygen content is 0 ppm).

[0152] There are different methods for adjusting the oxygen content in the solution or dispersion provided in step I) of method and for maintaining this low oxygen content during the polymerization reaction in step II).

[0153] According to one method, the solution or dispersion (or liquid component used to prepare the solution or dispersion) provided in step I) of method can be degassed, for example by introducing an inert gas such as N2, argon, CO2, or a mixture thereof into the solution or dispersion provided in step I) of method to reduce the initial oxygen content in the solution or dispersion. Alternatively, the solution or dispersion (or liquid component used to prepare the solution or dispersion) provided in step I) of method can be subjected to reduced pressure treatment to reduce the initial oxygen content, for example by stirring the solution or dispersion while applying a vacuum, or by sonication, or by a combination of reduced pressure treatment and sonication.

[0154] To ensure that a low oxygen content is maintained during the polymerization reaction in step II), the polymerization reaction can advantageously be carried out under an inert gas atmosphere, preferably under a N2 atmosphere, a CO2 atmosphere, an argon atmosphere, or a mixture of at least two of these inert gases. Oxidative polymerization in step II) can also advantageously be carried out at a pressure equal to or higher than the vapor pressure of the solution or dispersion during the polymerization reaction in step II). Preferably, the oxidative polymerization in step II) is carried out at a pressure at least 0.1 mbar higher than the vapor pressure of the solution or dispersion during the polymerization reaction in step II), more preferably at least 0.5 mbar, and most preferably at least 1 mbar. To ensure that a low oxygen content is maintained during the polymerization reaction in step II), the oxidative polymerization in step II) can also be carried out under reduced pressure, preferably at a pressure not exceeding 0.8 bar, and most preferably at a pressure not exceeding 0.5 bar.

[0155] Method 2 according to the present invention

[0156] Method 2 for preparing lamellar bodies also contributes to achieving the above objectives, and includes the following method steps:

[0157] A) Provide the substrate;

[0158] B) Apply the liquid polymer composition 1 or liquid polymer composition 2 according to the invention, preferably the liquid polymer composition 2 according to any one of the fifth to eighth embodiments, to at least a portion of at least one surface of the substrate;

[0159] C) Optionally, at least partially remove the solvent used to form a conductive layer that covers at least a portion of at least one surface of the substrate.

[0160] According to a particularly preferred embodiment of method 2 according to the invention, the substrate is the electrode body of the electrode material, wherein the dielectric at least partially covers one surface of the electrode material when forming the anode body. In such embodiments, method steps A) and B) therefore include the following method steps:

[0161] A) An electrode body is provided with an electrode material, wherein a dielectric material at least partially covers one surface of the electrode material when forming an anode body;

[0162] B) Introduce the polymer composition 1 or polymer composition 2 according to the invention, preferably the liquid polymer composition 2 according to any one of the fifth to eighth embodiments thereof, into at least a portion of the electrode body;

[0163] In step A), an electrode body of electrode material is first provided, wherein a dielectric material at least partially covers one surface of the electrode material to form an anode body.

[0164] In principle, the electrode body can be produced by pressing high-surface-area valve metal powder and sintering it to obtain a generally porous electrode body. Preferably, the electrical contact wires of the valve metal (such as, for example, tantalum) are also pressed into the electrode body. The electrode body is then coated with a dielectric (i.e., an oxide layer), for example by electrochemical oxidation. Alternatively, a metal foil can be etched and coated with a dielectric by electrochemical oxidation to obtain an anode foil with porous regions. In a wound capacitor, the anode foil with porous regions (which forms the electrode body) and the cathode foil are separated by a separator and wound together.

[0165] In the context of this invention, valve metals should be understood as those metals whose oxide layers do not allow current to flow evenly in both directions. When a voltage is applied at the anode, the oxide layer of the valve metal blocks the current, while when a voltage is applied at the cathode, a large current occurs, which can damage the oxide layer. Valve metals include Be, Mg, Al, Ge, Si, Sn, Sb, Bi, Ti, Zr, Hf, V, Nb, Ta, and W, as well as alloys or compounds of at least one of these metals with other elements. The most well-known representatives of valve metals are Al, Ta, and Nb. Compounds having electrical properties equivalent to valve metals are those that are metallic conductive, can be oxidized, and whose oxide layers have the aforementioned properties. For example, NbO has metallic conductivity but is not generally considered a valve metal. However, the layer of oxidized NbO has the typical properties of valve metal oxide layers, making NbO or alloys or compounds of NbO with other elements typical examples of such compounds having electrical properties equivalent to valve metals. Electrode materials containing tantalum, aluminum, and those based on niobium or niobium oxide are preferred. Tantalum and aluminum are preferred as electrode materials.

[0166] To produce electrode bodies that often have porous regions, valve metal can be sintered in powder form to obtain a typically porous electrode body, or the porous structure can be imprinted onto a metal body. The latter can be done, for example, by etching a foil.

[0167] For simplicity, a body having porous regions is also referred to as porous hereinafter. Therefore, for example, an electrode body having porous regions is also called a porous electrode body. In one aspect, a porous body can be permeated by multiple channels and is therefore sponge-like. This is often the case if tantalum is used in the construction of a capacitor. Furthermore, it is possible that only the surface has pores, and the subsequent region below the surface pores is structurally solid. This is often observed if aluminum is used in the construction of a capacitor. Preferably, the electrode body is porous.

[0168] The typically porous electrode body produced in this way is then oxidized by applying a voltage, for example, in a suitable electrolyte (such as an aqueous solution containing phosphoric acid or ammonium adipate), to form a dielectric. The level of this formation voltage depends on the thickness of the oxide layer to be achieved or the subsequent operating voltage of the capacitor. Preferred formation voltages are in the range of 1V to 1000V, particularly preferably in the range of 2V to 500V, and very particularly preferably in the range of 1V to 300V. According to a first embodiment of the method for producing a capacitor, the formation voltage is in the range of 1V to 20V, while according to a second embodiment of the method for producing a capacitor, the formation voltage is in the range of 30V to 100V.

[0169] The porous electrode body typically used preferably has a porosity of 10% to 90%, preferably 30% to 80%, particularly preferably 50% to 80%, and an average pore size of 10 nm to 10,000 nm, preferably 20 nm to 5,000 nm, particularly preferably 50 nm to 3,000 nm.

[0170] According to a specific embodiment of method 2 of the invention, the electrolyte capacitor to be produced is an aluminum wound capacitor. In this case, a porous aluminum foil is formed at the anode as the electrode material, and an alumina coating is formed as the dielectric. The aluminum foil (anode foil) obtained in this way is then provided with contact lines and wound with another, optionally porous aluminum foil (cathode foil) also provided with contact lines, the two foils being spaced apart from each other by one or more separators based, for example, cellulose or preferably based on synthetic paper. After being wound, the anode body obtained in this way is fixed, for example, by adhesive tape. The one or more separators can be carbonized by heating in an oven. This method and manner of producing the anode body of an aluminum wound capacitor is well known from the prior art and is described, for example, in US 7,497,879 B2.

[0171] According to another specific embodiment of method 2 of the present invention, the electrolyte capacitor to be produced is an aluminum stacked capacitor or a tantalum electrolyte capacitor (“tantalum electrolyte”), particularly a tantalum electrolyte capacitor having a polymer outer layer, such as described in DE-A-10 2009 007 594.

[0172] In step B) of method 2 according to the invention, polymer composition 1 or polymer composition 2 according to the invention, preferably polymer composition 2 according to any one of the fifth to eighth embodiments, is introduced into at least a portion of the anode body. In this context, it should be noted that other compositions, such as PEDOT / PSS dispersions, may be introduced into the anode body for forming a conductive layer before polymer composition 1 or polymer composition 2 is introduced into at least a portion of the anode body. Therefore, it is not necessarily required to apply polymer composition 1 or polymer composition 2 directly to at least a portion of the dielectric layer of the anode body.

[0173] Polymer composition 1 or polymer composition 2, preferably polymer composition 2 according to any one of the fifth to eighth embodiments, is introduced into the porous region by known methods such as impregnation, immersion, casting, dripping, spraying, misting, scraping, brushing, or printing (e.g., inkjet printing, screen printing, or pad printing). Preferably, introduction is performed by immersing the anode body in the polymer composition and thus impregnating it with the polymer composition. Immersion or impregnation with the polymer composition is preferably carried out over a period ranging from 1 second to 120 minutes, particularly preferably from 5 seconds to 60 minutes, and most preferably from 10 seconds to 15 minutes. Introducing the polymer composition into the anode body can be facilitated, for example, by increasing or decreasing pressure, vibration, ultrasound, or heat.

[0174] In method step B), the polymer composition 2 according to any one of the fifth to eighth embodiments, preferably used therein, may contain additional additives, such as surfactants, such as anionic surfactants, such as alkylbenzene sulfonic acids and salts, alkane sulfonates, alcohol sulfonates, ether sulfonates, sulfosuccinates, phosphate esters, alkyl ether carboxylic acids, or carboxylates; cationic surfactants, such as, for example, alkyl quaternary ammonium salts; and nonionic surfactants, such as, for example, linear alcohol ethoxylates, carbonyl synthetic alcohol ethoxylates, alkylphenol ethoxylates, or alkyl polyglucosides, particularly those that can be trademarked. and Commercially available surfactants; or adhesion promoters, such as, for example, organofunctional silanes or their hydrolysis products, such as 3-glycidoxypropyltrialkoxysilane, 3-amino-propyl-triethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, vinyltrimethoxysilane or octyltriethoxysilane; crosslinking agents, such as melamine compounds, masked isocyanates, functional silanes (e.g., tetraethoxysilane), alkoxysilane hydrolysis products (e.g., tetraethoxysilane-based), epoxysilanes (such as 3-glycidoxypropyltrialkoxysilane-polyurethane), polyacrylates or polyolefin dispersions.

[0175] In method step B), the polymer composition 2 according to any one of the fifth to eighth embodiments preferably used comprises additional additives that optionally increase conductivity, such as, for example, compounds containing ether groups, such as, for example, tetrahydrofuran; compounds containing lactone groups, such as γ-butyrolactone, γ-valerolactone; compounds containing amide or lactam groups, such as caprolactam, N-methylcaprolactam, N,N-dimethylacetamide, N-methylacetamide, N,N-dimethylacetamide, etc. Formamide (DMF), N-methylformamide, N-methylformanilide, N-methylpyrrolidone (NMP), N-octylpyrrolidone, pyrrolidone; sulfones and sulfoxides, such as, for example, sulfolane (tetramethylene sulfone), dimethyl sulfoxide (DMSO); sugars or sugar derivatives, such as, for example, sucrose, glucose, fructose, lactose; sugar alcohols, such as, for example, sorbitol, mannitol; furan derivatives, such as, for example, 2-furancarboxylic acid, 3-furancarboxylic acid, glycerol, diglycerol, triglyceride, or tetraglyceride.

[0176] The polymer composition 2, preferably used in step B) according to any one of the fifth to eighth embodiments, may further comprise one or more organic binders soluble in water or water-miscible solvents as additional additives. Furthermore, the polymer composition 2 may also comprise one or more compounds as additional additives that increase the thermal stability of the conductive layer, such as aromatic compounds having at least two OH groups, such as gallic acid (3,4,5-trihydroxybenzoic acid), tannic acid, or flavonoids.

[0177] In method step B), the polymer composition 2 according to any one of the fifth to eighth embodiments preferably used has a viscosity between 0.01 mPa·s and 1,000 mPa·s (measured using a rheometer at 20°C and 100 s). -1The viscosity (measured at a shear rate) depends on the method of application. Preferably, the viscosity is between 1 mPa·s and 500 mPa·s, particularly preferably between 1 mPa·s and 250 mPa·s. In the case of producing aluminum wound capacitors, the viscosity is very, particularly preferably in the range of 1 mPa·s to 200 mPa·s, while in the production of tantalum electrolyte capacitors or aluminum stacked capacitors, it is very, particularly preferably in the range of 1 mPa·s to 50 mPa·s. The viscosity can be adjusted, for example, by adding a suitable rheology modifier as an additional additive.

[0178] In method step B), the solids content of the polymer composition 2 according to any one of the fifth to eighth embodiments, preferably used in each case, is preferably in the range of 0.01 wt% to 20 wt% based on the total weight of the liquid polymer composition, particularly preferably in the range of 0.1 wt% to 15 wt%, and most preferably in the range of 0.25 wt% to 10 wt%. The solids content of the liquid polymer composition is determined by drying the liquid polymer composition at a sufficiently high temperature to remove the solvent or dispersant.

[0179] According to a particularly preferred embodiment of method 2 according to the invention, the polymer composition 2 introduced into the capacitor body according to any one of the fifth to eighth embodiments comprises not only a functionalized π-conjugated polymer, but also an externally doped conductive polymer in addition to the self-doped conductive polymer, preferably PEDOT / PSS, as disclosed in WO2014 / 048562 A2. The disclosure of WO 2014 / 048562A2 regarding the combined use of a self-doped polymer (such as PEDOT-S) and an externally doped polymer (such as PEDOT / PSS) for forming a solid electrolyte is incorporated herein by reference and forms part of the disclosure of this application.

[0180] After impregnating the anode body with the polymer composition 2 according to any one of the fifth to eighth embodiments as described above, it is advantageous to at least partially remove the solvent or dispersant contained in the polymer composition in the subsequent method step C), thereby forming a solid electrolyte that completely or partially covers the dielectric, and thus forming the capacitor body. In this context, it is preferred that the solid electrolyte covers the dielectric at least 10%, particularly preferably at least 25%, and most preferably at least 50%, which can be determined by measuring the capacitance of the capacitor at 120 Hz in dry and wet conditions, as described in DE-A-10 2005 043 828.

[0181] Removal or hardening is preferably carried out by removing and drying the solvent from the polymer composition, preferably at a temperature in the range of 20°C to 260°C, particularly preferably in the range of 50°C to 220°C, and most preferably in the range of 80°C to 200°C. Alternatively, the solvent or dispersant may be at least partially removed by freeze-drying. Steps B) and C) may also be repeated once or more to adapt the thickness of the solid electrolyte layer deposited on the dielectric or the electrolyte filler density in the electrode body to specific requirements.

[0182] After the capacitor bodies are manufactured in this manner, they can be further modified using methods and techniques known to those skilled in the art. In the case of tantalum electrolyte capacitors, the capacitor body can be covered, for example, with a polymer outer layer as described in DE-A-10 2004022674 or DE-A-10 2009 007 594, and / or with a graphite and silver layer as known from DE-A-10 2005 043 828, while in the case of aluminum wound capacitors according to the teachings of US 7,497,879B2, the capacitor body is bonded to an aluminum beaker, provided with a sealing glass, and mechanically sealed securely by compression. The capacitor can then be conditioned in a known manner to prevent defects in the dielectric by aging.

[0183] The invention will now be explained in more detail with reference to the non-limiting drawings and examples.

[0184] Figure 1 The correlation between the conductivity of the conductive layer prepared by means of the PEDOT-S composition according to the invention and the content of sodium 3-butene-1-sulfonate in the EDOT-S monomer solution from which PEDOT-S is prepared is shown.

[0185] Figure 2 This shows sodium 3-butene-1-sulfonate (butene-S Na). 1 H NMR spectrum (D2O).

[0186] Figure 3 The image shows a mixture of butene-SNa (top) and butene-SNa-rich EDOT-SNa monomer products (bottom). 1 Comparison of H NMR spectra (D2O).

[0187] Test methods

[0188] UV / VIS - Measurement of Spectra (Transmission) and Color Values ​​b*

[0189] Color value b* was determined according to ASTM E 308-13.

[0190] Prior to measurement, a 1% by weight solution of the given functionalized thiophene monomer was prepared using completely deionized water until a completely dissolved solution was obtained. Transmission spectra were acquired using a Perkin Elmer Lambda900 UV / VIS / NIR spectrometer at a resolution of 5 nm / data point. The lamp was allowed to run for 30 minutes prior to measurement.

[0191] All spectra were generated using quartz glass cuvettes (0.5 mm). Background transmission spectra (200 nm to 2500 nm) were obtained using fully deionized water to generate a baseline spectrum. Then, the 1% solution was measured. After generating the transmission spectra, the color values ​​b* were determined using WinCol software with a D65 light source and a 10° observer.

[0192] With the help of 1 H NMR determination of unsaturated organic sulfonic acid content

[0193] The content of unsaturated organic sulfonic acids, especially sodium 3-butene-1-sulfonate, in the composition of functionalized thiophene monomers is determined by... 1 H NMR is determined by the presence of characteristic peaks. Table 1 shows these characteristic peaks for 3-butene-1-sulfonate (butene-S Na).

[0194] Proton identity <![CDATA[ 1 H NMR shift / ppm]]> Proton counting 1 5.14 2H 2 5.95 1H 3 2.52 2H 4 3.03 2H

[0195] Table 1: Sodium 3-butene-1-sulfonate 1 H NMR signal

[0196]

[0197] The integrals of the aromatic thiophene protons of EDOT-S Na and ProDOT-S Na (6.53 ppm and 6.74 ppm, respectively) and the integrals of the terminal olefin protons (1) allow for the determination of the corresponding three-component molar ratios (EDOT-S Na, ProDOT-S Na and butene-SNa).

[0198] Conductivity

[0199] A clean glass substrate measuring 50 mm × 50 mm was placed on a spin coater, and 10 ml of the liquid composition according to the invention was distributed onto the substrate. The remaining solution was then spin-coated off using a rotating plate. The coated substrate was then dried on a hot plate at 130°C for 15 minutes. The layer thickness was then measured using a layer thickness measuring device (Tencor, Alphastep 500). The conductivity was measured by vapor deposition of a 25 mm long Ag electrode at a distance of 10 mm using a shadow mask. The surface resistance measured using an electrometer (Keithly 614) was multiplied by the layer thickness to obtain the resistivity. The conductivity is the reciprocal of the resistivity.

[0200] average value

[0201] Unless otherwise specified, the average corresponds to the arithmetic mean.

[0202] Solid content

[0203] Solids content was determined by gravimetric analysis using a precision balance (Mettler AE 240). First, the empty weighing bottle, including the cap, was weighed (weight A). Then, 3g of the dispersion to be analyzed was filled into the bottle, the cap was sealed, and the bottle was weighed again to determine the precise total weight (weight B). The bottle was placed in a ventilated drying oven (Memmert UNB200) at 100°C for 16 hours. When removing the sample bottle from the oven, it is important to immediately cover it with the glass cap due to the hygroscopic nature of the dry dispersion. After a cooling period of 10 to 15 minutes, the bottle (including the cap) was weighed again to determine weight C. At least two repetitions were always performed to allow for the determination of the average solids content. Example

[0204] Example 1: Synthesis of EDOT-MeOH / ProDOT-MeOH (not part of this invention)

[0205] The precursor compounds of EDOT-MeOH and EDOT-S Na are produced by a multi-step synthesis of dimethyl 3,4-dihydroxythiophene-2,5-dicarboxylic acid, according to Chevrot et al. (J. Electroanalytical. Chem.) 1998, 443, 217-226. The synthesis proceeds in the following three steps:

[0206] Step 1

[0207] Dimethyl 3,4-dihydroxythiophene-2,5-dicarboxylic acid (14.0 g, 54 mmol) was dissolved in ethanol (270 mL) and heated to reflux. Then, under reflux, a solution of epibromopropane (6 mL, 70 mmol) and potassium carbonate (1.5 g, 11 mmol) in distilled water (80 mL) was added to the reaction solution. The mixture was refluxed for 1 hour, and then additional amounts of epibromopropane (10.4 g, 122 mmol) and potassium carbonate (0.8 g, 6 mmol) were added. The reaction was refluxed again for 72 hours. The resulting solution was extracted twice with chloroform (200 mL). The organic layer was then washed with a 5% potassium chloride aqueous solution (200 mL). The organic phase was dried over MgSO4 and filtered, and the solvent was removed by rotary evaporation under vacuum. A yellow solid was obtained, which was recrystallized from diethyl ether (100 mL) to give a white crystalline powder (intermediate 1, 78% yield). Intermediate 1 was obtained at a ratio of approximately 90:10 of six-membered ring (EDOT): seven-membered ring (ProDOT).

[0208] Intermediate 1: Thiophene[3,4-b]-1,4-dioxin-5,7-dicarboxylic acid, 2,3-dihydro-2-(hydroxymethyl)-5,7-dimethyl ester and isomer.

[0209] Step 2

[0210] Intermediate 1 (11.54 g, 36 mmol) from step 1 was added to a solution of potassium hydroxide (12 g; 214 mmol) in distilled water (250 mL). After the reactants were completely dissolved, the solution was heated to reflux for 2 hours. The volume of the solution was then reduced to 100 mL by rotary evaporation. Concentrated HCl (24 mL) was slowly added to the cooled solution (ice bath) with continuous stirring. After 2 hours, the white precipitate was separated by filtration and dried under vacuum at 80 °C to give a light gray powdery solid intermediate 2 (9.22 g, 35 mmol, 97%).

[0211] Intermediate 2: 2,3-dihydro-2-(hydroxymethyl)thieno[3,4-b]-1,4-dioxin-5,7-dicarboxylic acid and its isomer.

[0212] Step 3

[0213] Intermediate 2 (9.22 g, 35 mmol) from step 2 was mixed with copper chromite catalyst (1 g, 3.2 mmol) and freshly distilled quinoline (50 mL). The suspension was refluxed at 180 °C for 2 hours under nitrogen. After cooling, diethyl ether was added, and insoluble precipitates were removed by filtration. The subsequent filtrate was washed with 5% HCl and 5% potassium chloride solution. The organic phase was dried over MgSO4, filtered, and the filtrate was concentrated by rotary evaporation. The resulting residue was purified by column chromatography (diethyl ether:cyclohexane (95:5)) to obtain 2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol (EDOT-MeOH) (3.22 g, 19 mmol, 54%).

[0214] The final EDOT-MeOH:ProDOT-MeOH ratio was obtained at approximately 90:10 (e.g., via...). 1 (H NMR determination).

[0215] Example 2: Synthesis of EDOT-S Na / ProDOT-S Na including olefins (not of this invention)

[0216] To prepare the EDOT-S Na monomer with sulfonic acid side chains, the product EDOT-MeOH of Example 1 was reacted in an additional step according to Chevrot et al. (J. Electroanal. Chem.) 1998, 443, 217-226.

[0217] Sodium hydride (0.38 g, 16 mmol, 60% oil dispersion) was added to anhydrous toluene (50 mL) and the mixture was stirred continuously under a nitrogen atmosphere. EDOT-MeOH (2.24 g, 13 mmol) prepared as in Example 1, dissolved in toluene (20 mL), was slowly added under vigorous stirring. The reaction mixture was heated to reflux for 1 hour. Then, 1,4-butanesulfonyl lactone (1.8 g, 13 mmol) dissolved in 15 mL of toluene was slowly added dropwise to the stirred solution. The reaction was refluxed again for 2 hours and stirred at room temperature for 17 hours. Acetone (200 mL) was added under vigorous stirring. The resulting suspension was filtered through a sintered filter and washed with additional acetone under a nitrogen atmosphere. The product was vacuum dried at 40 °C to obtain an orange / off-white powder, “Sample #1” (3.7 g, 11.2 mmol, 86%).

[0218] For Example 2, the ratio of the resulting product mixture of EDOT-S Na:ProDOT-S Na:butene-S Na (=sodium 3-butene-1-sulfonate) was approximately 77.9:16.7:5.4 (as per [previous description]). 1 (H NMR determination).

[0219] Example 3: Purification of EDOT-S Na (This Invention)

[0220] The product mixture (30 g) obtained in Example 2 was dissolved in distilled water (30 g) at 80 °C for up to 1 hour or until a 50% by mass solution was obtained. The solution was filtered to remove undissolved solids. The solution was cooled to room temperature. EtOH (100 mL) was externally cooled by dry ice (-40 °C) while stirring, and EDOT-S Na solution was added dropwise over 30 minutes, followed by stirring for another hour. The subsequent suspension was filtered through a sintered filter, and the yellow solid was dried in a vacuum chamber (50 °C) for at least 3 days to obtain “Sample #2” (recovery mass = 93%).

[0221] EDOT-S Na with reduced olefin content was obtained at a molar ratio of approximately 80:17:3 for EDOT-S Na:ProDOT-S Na:Butene-S Na (e.g., by means of...). 1 (H NMR determination).

[0222] Example 4: Purification of EDOT-S Na (This Invention)

[0223] The product mixture (50 g) obtained in Example 2 was dissolved in distilled water (50 g) at 80 °C for up to 1 hour or until a 50% by mass solution was obtained. The solution was filtered to remove undissolved solids. The solution was cooled to room temperature. EtOH (350 mL) was externally cooled by dry ice (-20 °C) while stirring, and EDOT-S Na solution was added dropwise over 2 to 3 hours, followed by stirring for another hour after the addition. The subsequent suspension was filtered through a sintered filter, and the yellow solid was dried in a vacuum chamber (50 °C) for at least 3 days to obtain “Sample #3” (recovery mass = 68%).

[0224] EDOT-S Na with reduced olefin content was obtained at a molar ratio of approximately 84:15:1.2 of EDOT-S Na:ProDOT-S Na:butene-S Na (e.g., by means of...). 1 (H NMR determination).

[0225] Example 5: Purification of EDOT-S Na (This invention)

[0226] The product mixture (5 g) obtained in Example 2 was dissolved in distilled water (20 g) at 80 °C for 1 hour or until a 20% by mass solution was obtained. The solution was filtered to remove undissolved solids. The solution was cooled to room temperature. nBuOH (250 mL) was externally cooled by dry ice (-40 °C) while stirring, and EDOT-S Na solution was added dropwise over 30 minutes, followed by stirring for another hour. The subsequent suspension was filtered through a sintered filter, and the yellow solid was dried in a vacuum chamber (50 °C) for at least 3 days to obtain “Sample #4” (recovery mass = 42%).

[0227] EDOT-S Na with reduced olefin content was obtained at a molar ratio of approximately 99:0.5:0.75 of EDOT-S Na:ProDOT-S Na:butene-S Na (e.g., by means of...). 1 (H NMR determination).

[0228] Example 6: Purification of EDOT-S Na (This invention)

[0229] The product mixture (20 g) obtained in Example 4 was dissolved in distilled water (30 mL) at 80 °C for 1 hour or until a 40% by mass deep orange solution was obtained, and then slowly cooled to room temperature. The solution was then cooled to 9 °C using a thermostatically controlled cooling system and held for approximately 48 hours, during which a precipitate was observed. The precipitate was filtered through a sintering filter and subsequently dried in a vacuum chamber (50 °C) for at least 3 days to obtain a pale yellow solid as “Sample #5” (recovery mass = 58%).

[0230] After purification steps B and D, high-purity EDOT-S Na (total recovery mass = 39%) was obtained, wherein the molar ratio of EDOT-S Na:ProDOT-S Na:butene-S Na was approximately 98.5:1.5:0 (e.g., via purification steps B and D). 1 (H NMR determination).

[0231] Example 7: Polymerization of the product mixture formed in Example 2 (not of this invention)

[0232] The product mixture (5.00 g) obtained in Example 2 was dissolved in distilled water (25 mL) and degassed with nitrogen for 60 minutes while cooling to 10°C. Ferric(III) sulfate (0.8 g, 2 mmol) was dissolved in distilled water (5 mL) and degassed with nitrogen for 30 minutes. The ferric(III) sulfate solution was then added to the EDOT-S Na solution in one step. DMSO (30 mg, 0.38 mmol) was then added to this solution as well. Sodium persulfate (3.98 g, 16.7 mmol) was added to distilled water (10 mL) and degassed with nitrogen for 60 minutes. The reaction solution was stirred throughout, and the temperature was maintained at 10°C throughout the slow addition of the sodium persulfate solution. The reaction proceeded for 17 hours while being heated to room temperature, and then the solution was added to the ion exchanger ( S108H and MP 62 was prepared and the mixture was stirred at room temperature for 30 minutes. This process was repeated three times, with filtration after each round. After the ion exchanger had been filtered out, the solution was diluted to a solids content of 0.87%. Subsequent sonication yielded a deep blue polymer solution.

[0233] Example 8: Polymerization of the product mixture formed in Example 3 (This invention)

[0234] The product mixture (5.00 g) obtained in Example 3 was polymerized according to the scheme outlined in Example 7 to obtain a dark blue polymer solution with a solid content of 1.10%.

[0235] Example 9: Polymerization of the product mixture formed in Example 4 (This invention)

[0236] The product mixture (5.00 g) obtained in Example 4 was polymerized according to the scheme outlined in Example 7 to obtain a dark blue polymer solution with a solid content of 1.07%.

[0237] Example 10: Polymerization of the product mixture formed in Example 5 (This invention)

[0238] The product mixture (5.00 g) obtained in Example 5 was polymerized according to the scheme outlined in Example 7 to obtain a dark blue polymer solution with a solid content of 1.16%.

[0239] Example 11: Polymerization of the product mixture formed in Example 6 (This invention)

[0240] The product mixture (5.00 g) obtained in Example 6 was polymerized according to the scheme outlined in Example 7 to obtain a dark blue polymer solution with a solid content of 1.2%.

[0241] Table 2 shows the purity ratio (EDOT-S Na:ProDOT-S Na:Butene-S Na) and color value b* of the product mixtures prepared according to Examples 2 to 6. Table 3 shows the polymer film conductivity and solids content % of each corresponding polymer dispersion produced according to Examples 7 to 11.

[0242]

[0243] Table 2: EDOT-S, Na:ProDOT-S, and Na:Butene-S of the thiophene monomers produced in Examples 2 to 6 Na Ratio and color value b*

[0244]

[0245] Table 3: Thin film conductivity and solids content of PEDOT-S dispersions produced in Examples 7 to 11

[0246] Figure 1 The relationship between the conductivity of a given film and the olefin content of the original EDOT-S Na monomer product mixture is shown. This graph illustrates the requirement for a low olefin content percentage to achieve higher conductivity in the final film.

Claims

1. A monomer composition comprising at least one functionalized thiophene monomer having structure I in X 1 and X 2 Independently of each other, they represent O or S; X 3 represents CH2-O, where the carbon atom is bonded to R 1 , or represents O; R 1 represents a trivalent organic group; R 2 represents a divalent organic group; M 1 represents a monovalent cation; wherein the monomer composition is substantially free of an unsaturated organic sulfonic acid having structure II in R 3 represents a divalent organic group; M 2 represents a monovalent cation; Alternatively, the monomer composition comprises an unsaturated organic sulfonic acid having the structure II in a maximum amount such that the molar ratio of the total amount of the unsaturated organic sulfonic acid having the structure II to the total amount of the functionalized thiophene monomer having the structure I is 1:32 or less.

2. The monomer composition according to claim 1, wherein the monomer composition comprises a functionalized thiophene monomer having structure Ia or structure Ib or a mixture of functionalized thiophene monomers having structure Ia or Ib Wherein in Formula Ia and Ib -m is 2 and R 3 is -CH3; or -m is 3 and R 3 For H.

3. The monomer composition according to claim 2, wherein in formula Ia and Ib, m is 3 and R 3 For H.

4. The monomer composition according to any one of claims 1 to 3, wherein the monomer composition comprises a functionalized thiophene monomer having the structure I in an amount of at least 90 wt % based on the total weight of the monomer composition.

5. The monomer composition according to claim 4, wherein the monomer composition satisfies at least one of the following characteristics: i) the monomer composition has a color value b* of less than 0.75 as determined according to ASTM E 308-13, the color value being determined using an aqueous solution containing 1% by weight of the at least one functionalized thiophene monomer having the structure I in a 0.5 mm transmission quartz glass cuvette; ii) The transmittance of the monomer composition measured for light having a wavelength of 350 nm is at least 90%.

6. A method for preparing a polymer composition comprising a functionalized π-conjugated polythiophene, the method comprising the following method steps: I) dissolving or dispersing the monomer composition according to any one of claims 1 to 5 in a solvent or dispersant to obtain a solution or dispersion of the functionalized thiophene monomer; II) oxidatively polymerizing the functionalized thiophene monomer having the structure I in the solution or dispersion provided in method step I) to obtain a polymer composition in the form of a solution or dispersion, wherein the polymer composition comprises a functionalized π-conjugated polythiophene, wherein the functionalized π-conjugated polythiophene comprises repeating units having the structure I' The asterisk (*) indicates a bond to an adjacent repeating unit.

7. A polymer composition comprising a functionalized π-conjugated polythiophene, wherein the functionalized π-conjugated polythiophene comprises a repeating unit having the structure I' in X 1 and X 2 Independently of each other, they represent O or S; X 3 represents CH2-O, where the carbon atom is bonded to R 1 , or represents O; R 1 represents a trivalent organic group; R 2 represents a divalent organic group; M 1 represents a monovalent cation; Wherein the asterisk (*) indicates a bond to an adjacent repeating unit; wherein the functionalized π-conjugated polythiophene is substantially free of repeating units having structure II' in R 3 represents a divalent organic group; M 2 represents a monovalent cation; Wherein the asterisk (*) indicates a bond to an adjacent repeating unit; Or wherein the functionalized π-conjugated polythiophene comprises repeating units having the structure II' in a maximum amount such that the molar ratio of the total amount of repeating units having the structure II' to the total amount of repeating units having the structure I' is 1:32 or less.

8. The polymer composition according to claim 7, wherein the functionalized π-conjugated polythiophene comprises a repeating unit having structure Ia' or structure Ib' or a mixture of repeating units having structure Ia' or Ib' Wherein in formula Ia' and Ib' -m is 2 and R 3 is -CH3; or -m is 3 and R 3 For H.

9. The polymer composition according to claim 7 or 8, wherein in formula Ia' and Ib', m is 3 and R 3 For H.

10. The polymer composition according to any one of claims 7 to 9, wherein the polymer composition is a liquid polymer composition further comprising at least one solvent or dispersant, wherein the liquid polymer composition comprises the functionalized π-conjugated polythiophene in an amount ranging from 0.1 wt % to 25 wt % based on the total weight of the liquid polymer composition.

11. The polymer composition according to any one of claims 7 to 9, wherein the polymer composition is a conductive layer, wherein the conductive layer comprises the functionalized π-conjugated polythiophene in an amount ranging from 50 wt% to 99.9 wt% based on the total weight of the conductive layer.

12. A method for preparing a layered body, the method comprising the following method steps: A) providing a substrate; B) applying the polymer composition according to claim 10 to at least a portion of at least one surface of the substrate; C) optionally at least partially removing the solvent or dispersant used to form a conductive layer covering at least a portion of at least one surface of the substrate.

13. The method of claim 12, wherein the substrate is an electrode body of an electrode material, wherein a dielectric at least partially covers one surface of the electrode material when forming an anode body.

14. Use of the monomer composition according to any one of claims 1 to 5 or the polymer composition according to any one of claims 7 to 11 for preparing a conductive layer in an electronic device.

15. The use according to claim 14, wherein the electronic device is selected from the group consisting of OLED, coated fabrics, photoconductive cells, photoresistors, photoelectric switches, phototransistors, phototubes, IR detectors, optoelectronic devices, solar cells, coating materials for memory storage devices, field effect resistor devices, antistatic films, biosensors, electrochromic devices, solid electrolyte capacitors, energy storage devices, touch panels and electromagnetic shielding.

Citation Information

Patent Citations

  • Electrolytic condenser for use in electronic circuits, e.g. for computers, comprises porous electrode, dielectric, solid electrolyte and a layer containing a polymeric anion, a polyaniline or polythiophene and a binder

    DE102004022674A1

  • method of manufacturing electrolytic capacitors

    DE102005043828A1

  • Method for manufacturing electrolytic capacitors with a polymer outer layer.

    DE102009007594A1

  • Solid electrolyte and electrolytic capacitor using the same

    EP0340512A2

  • Method for making pi-conjugated water soluble polymers

    EP1122274A1

Cited By

  • Method for improving conductivity of water-soluble self-doped polymer through acid-adding reflux post-treatment

    CN121248906A